Penggunaan Media Digital Untuk Rekonstruksi Peristiwa Sejarah Pada Mata Pelajaran Sejarah Kebudayaan Islam Di MAN 2 Mataram - Fitria Suryaningsih; Fransiska Khumaira (Educational Note, 2025)
This study aims to examine the effectiveness of using digital media in the process of reconstructing historical events in the Islamic Cultural History (SKI) subject at MAN 2 Mataram. In the context of 21st-century education, the integration of technology has become an urgent necessity to enhance student engagement and understanding of learning materials, particularly in subjects related to history. Digital media such as documentary videos, animations, digital simulations, and interactive platforms are considered capable of presenting past events in a more visual and contextual manner. This research employs a qualitative approach using a case study method. Data collection techniques include classroom observations, interviews with teachers and students, and analysis of learning documents. The results show that the use of digital media can increase students’ learning interest, facilitate understanding of the chronology and context of historical events, and foster critical and appreciative attitudes toward Islamic cultural heritage. Teachers also find it easier to convey complex materials in a simpler and more engaging way. However, challenges such as limited technological infrastructure and teachers’ digital literacy remain obstacles to optimal implementation. Therefore, training in digital media usage for teachers and improvement of learning facilities are necessary considerations. In conclusion, digital media is a potential tool for reconstructing historical events in SKI subjects, supporting active and meaningful learning in the digital era.